Studi Inhibisi Korosi Baja oleh Ekstrak Biji Kakao (Theobroma cacao) dalam Medium Asam Klorida - Nurfitriana .; Irma Mon; Yerimadesi Busmairizal (Departemen Kimia FMIPA UNP, 2012)
Cocoa (Theobroma cacao) is one of the many plants contain catechin. Catechin can form a complex with iron, a complex is formed on the surface of steel and the complex adsorbed may block the entry of oxygen, ions Cl- ion and other corrosive, so the rate of corrosion can be slowed down. This research aims to determine the efficiency of inhibition corrosion of steel by cocoa extract in hydrochloric acid medium. The method used is based on the gravimetric, namely based on the reduction of weight (weight loss) of steel before and after with corrosion. Surface analysis the steel is done using stereo microscopes. Of research results obtained that the cacao seed extract may decrease the rate of corrosion of steel in hydrochloric acid medium 0.01 M with corrosion inhibition efficiency 76,21% and results analysis by FTIR spectrophotometer to layer on steel surface indicate a complex formed between Fe-catechin.